Basal Area, Soil, and Elevation Factors Affecting The Essential Oils Yield, Geranyl Acetate, and D-Limonene of Zanthoxylum acanthopodium - Kintamani, Endang; Kusmana, Cecep; Tiryana, Tatang; Mirmanto, Edi; Batubara, Irmanida (Trends in Sciences, 2024)
Andaliman (Z. acanthopodium) is an aromatic Non-Timber Forest Product (NTFP) plant species that contains essential oils (EOs), which have various benefits for cuisine, medicine, and cosmetics. This study is essential because it is not yet known what biotic factors (basal area) and abiotic factors (soil and elevation) influence the EOs yield, geranyl acetate, and D-limonene as skin anti-aging. This study investigated whether the basal area, soil, and elevation factors influence the EOs yield, geranyl acetate, and D-limonene content of Andaliman fruit. The biotic and abiotic factors were measured from 9 sample plots representing the Andaliman habitats in North Sumatra, Indonesia. A vegetation analysis was conducted to derive the Andaliman basal area of each sample plot. Soil samples were taken randomly in each plot and analyzed for their physicochemical (pH, C, SOM, N, CNR, P, K, Ca, Mg, CEC, BS, SA, DU, CL, WC, and BD) contents. Elevation gradients were measured on each plot. The EOs of Andaliman fruit include yield, geranyl acetate, and D-limonene as skin anti-aging. The data were analyzed using Partial Least Square Regression for Generalized Linear Models (PlsRglm) to determine which biotic and abiotic factors influenced the EOs yield, geranyl acetate, and D-limonene. This study confirmed that clay soil texture was the main factor influencing EOs of Andaliman fruit yield, geranyl acetate, and D-limonene. Apart from soil factors, basal area, and elevation factors were also essential to consider when cultivating Andaliman fruit as a source of skin anti-aging substances. HIGHLIGHTS To the best of the authors’s knowledge, the first study in Indonesia 2024 that integrated biotic and abiotic factors affecting the essential oils (EOs) yield, geranyl acetate and D-limonene contents derived from of acanthopodium fruit as skin anti-aging substance. Using Partial Least Square Regression for Generalized Linear Models (PlsRglm) method for analyzing basal area, soil factors and elevation that influence the EOs of acanthopodium fruit. Of all the abiotic and biotic factors studied, Clay soil texture is the most critical factor that influences acanthopodium fruit EOs as skin anti-aging substances. Basal area and elevation are also essential factors in the cultivation of aromatic Andaliman plants. GRAPHICAL ABSTRACT